Sosialisasi Pemanfaatan Media Pembelajaran Digital dalam Pembelajaran IPS Sekolah Dasar untuk Menghadapi Era Pendidikan Abad ke-21 - Arina Wulandari; Muhammad Arifin; Wulida Makhtuna; Dodit Enggar Wibowo (Jurnal Abdi Masyarakat dan Pemberdayaan Inovatif, 2026)
This community service program aimed to improve elementary school teachers' knowledge and competence in utilizing digital learning media for Social Studies (IPS) instruction to meet the demands of 21st-century education. The activity was conducted at SDN 5 Sungai Besar Banjarbaru and involved 15 teachers as participants. The implementation consisted of preparation, socialization sessions, demonstrations of digital learning media, interactive discussions, mentoring, and evaluation. The training materials covered the concept of digital learning, the importance of teachers' digital literacy, the utilization of digital media in Social Studies learning, and practical demonstrations using several digital platforms, including Canva, Quizizz, Google Forms, Google Maps, and YouTube Edu. The program evaluation employed a participant response questionnaire to measure teachers' understanding and readiness after participating in the activity. The evaluation results indicated an average participant satisfaction score of 91%, categorized as excellent. The highest score was obtained for the perceived benefits of the program (95%), while teachers' readiness to implement digital learning media reached 87%. The discussion session also revealed several challenges, including limited time, insufficient experience in using digital applications, and the lack of appropriate digital learning resources for Social Studies instruction. Nevertheless, the socialization program successfully enhanced teachers' knowledge, motivation, and confidence in integrating technology into classroom learning. This activity contributed positively to strengthening teachers' digital competence and served as an initial step toward implementing more innovative, interactive, contextual, and technology-based Social Studies learning in elementary schools. Continuous practical training and mentoring are recommended to ensure the sustainable integration of digital learning media into classroom practice.